Mental development of preschool and primary school children during the COVID-19 pandemic - D.A. Bukhalenkova; D.M. Nechaeva (Современная зарубежная психология, 2022)
The analytical review focuses on factors affecting the development of children during the COVID-19 pandemic. The results of 14 studies from 2020 to 2022 are systematized. The generalization of their results expands and clarifies the understanding of the relationship between the development process of preschool children with factors of relations between children and parents, the stress situation, forced isolation during a pandemic. The analyzed studies indicate that the stress level of parents and their perception of a stressful situation simultaneously affect the child’s perception of parents and the relationship with him. Empirical evidence has been systematized in favor of children attending kindergartens, educational centers, or taking help from other relatives as positively telling on their social development motor activity and comfortable family climate. It is emphasized that during the pandemic, the amount of screen time among younger schoolchildren has significantly increased.